Androcentric Rules in the Use of Address Term in Sasak Folklore - Titik Ceriyani Miswaty; Taufik Suadiyatno; Sutarman Sutarman (Jurnal Sinestesia, 2023)
This research aims to analyze the application of androcentric rules in the usage of address terms in Sasaknese folklore. Folklore encompasses oral traditions, myths, legends, songs, dances, and rituals that are inherited from generation to generation. It often reflects the history, values, and worldview of a community, which provides insights into its cultural heritage. This research utilizes a descriptive qualitative approach in which the data used consists of language used in folklore. Ten elders are involved as expert triangulation in the storytelling process to ensure the reliability of the folklore. The result of this research provides evidence of deep-rooted androcentrism and it can be seen from the usage of address terms that are used in the data of this research. It also proves how the culture of society is reflected in its language and mirrored in its literary works.